Xylazine spreads across the US: A growing component of the increasingly synthetic and polysubstance overdose crisis - Friedman, Joseph; Montero, Fernando; Bourgois, Phillippe; Wahbi, Rafik; Dye, Daniel; Goodman-Meza, David; Shover, Chelsea (Drug and alcohol dependence, 2022)
Sharp exacerbations of the US overdose crisis are linked to polysubstance use of synthetic compounds. Xylazine is a veterinary tranquilizer, long noted in the street opioid supply of Puerto Rico, and more recently Philadelphia. Yet its national trends, geographic distribution, and health risks are poorly characterized. In this sequential mixed-methods study, xylazine was increasingly observed by ethnographers in Philadelphia among drug-sellers and people who inject drugs (PWID). Subsequently, we systematically searched for records describing xylazine-present overdose mortality across the US and assessed time trends and overlap with other drugs. In 10 jurisdictions – representing all four US Census Regions – xylazine was increasingly present in overdose deaths, rising from 0.36% of deaths in 015m 6.7% in 2020. The highest xylazine prevalence data was observed in Philadelphia, (25.8% of deaths), followed by Maryland (19.3%) and Connecticut (10.2%). Illicitly-manufactured-fentanyls were present in 98.4% of xylazine-present-overdose-deaths – suggesting a strong ecological link – as well as cocaine (45.4%), benzodiazepines (28.4%), heroin (23.3%), and alcohol (19.7%). PWID in Philadelphia described xylazine as a sought-after adulterant that lengthens the short duration of fentanyl injections. They also linked it to increased risk of soft tissue infection and naloxone-resistant overdose. Xylazine is increasingly present in overdose deaths, linked to the proliferation of illicitly-manufactured-fentanyls. Ethnographic accounts associate it with profound risks for PWID. Nevertheless, many jurisdictions do not routinely test for xylazine, and it is not comprehensively tracked nationally. Further efforts are needed to provide PWID with services that can help minimize additional risks associated with a shifting drug supply. •Xylazine (veterinary tranquilizer) increasingly involved in overdose in all Census Regions.•Among 10 jurisdictions, prevalence rose from 0.36% of overdose deaths in 2015 to 6.7% in 2020.•Fentanyl was found in 98% of xylazine-involved deaths, suggesting strong link.•Ethnographic data suggest xylazine increases short duration of fentanyl, adds euphoria.•Xylazine presents novel health risks, e.g. abscesses, naloxone-resistant overdose.